LAND PROCUREMENT FOR PUBLIC INTEREST DEVELOPMENT IN INDONESIA - Prayitno, Budi; Priyoto, '; Sri Marleni, ' (Jurnal Privat Law, 2024)
This research aims to identify the rules and processes of land procurement for public interest development in Indonesia. The government of Indonesia, regardless of its leadership, is responsible for organizing development, including public interest development. In this process, land plays a crucial role as the location for the development. Understanding the rules and procedures of land procurement for public interest development is crucial. The process of land procurement is not as simple as it may seem and can be a significant obstacle in the development process. The researcher used a descriptive qualitative method and obtained data through library research. The primary data consists of regulations on land procurement for public interest development. The research concludes that regulations for land procurement in Indonesia for public interest development can be found in various levels of legislation, including laws and government regulations. The process consists of four steps: planning, preparation, implementation, and submission of the results.